Assessing soft skills components in science and technology programs within Malaysian Technical Universities - Mohd Salleh, Kahirol; Sulaiman, Nor Lisa; Mohamad, Mimi Mohaffyza; Lai, Chee Sern (Songklanakarin Journal of Science and Technology (SJST), 2017)
The workforce is a social environment where particular skills are essential in order for workers to perform well, have a competitive edge and succeed in their careers. A soft skill is one of the skills needed in every type of workplace setting. Soft skills include communication skills, collaboration skills, entrepreneurship, and others. Workplace need workers who are competent not only with technical skills but who also have soft skills. There is lack of literature discussion on the perceptions of needed soft skills in the workplace. Therefore, this study aimed to close the gap in the literature concerning the perceptions of instructors and students in the area of soft skills especially in communication skills, collaboration skills, and entrepreneurship at the workplace. This study aims to decrease the divide in soft skills differences among instructors and students in higher learning institutions so that students have the opportunity to excel in their learning process. This study employs quantitative method specifically using survey as an instrument. The findings shows soft skills including communication, collaboration, and entrepreneurship skills are one of the aspects stressed by the students and instructors at higher learning institutions to ensure that graduates will be employable and competent in order to contribute to the nation development.